Ocular disorders in children exposed in utero to buprenorphine. (2nd November 2021) - O'Connor, Alane B.; O'Brien, Liam M.; Rifai, Taunia; Ballem, Georgia; Housman, Sarah; Devore, Nathan; Schumacher-Feero, Linda
ABSTRACT: Objective : The national prevalence of pregnant women with opioid use disorder (OUD) increased from 1.5 per 1, 000 delivery hospitalizations in 1999 to 6.5 in 2014. Relatively little is known about post infancy outcomes in children exposed to buprenorphine during pregnancy. The objective of this study was to determine the presence of strabismus and reduced visual acuity in children exposed to buprenorphine during pregnancy. Methods : Retrospective matched cohort study of 153 exposed infants and 153 unexposed infants matched on demographic characteristics. Results : Exploratory modeling found exposure to buprenorphine during pregnancy (OR = 3.54; 95% CI: (1.26, 9.94); p < .02), exposure to cigarettes during pregnancy (OR = 3.34; 95% CI: (1.09, 10.2); p < .04) and male gender (OR = 2.68; 95% CI: (1.01, 7.12); p < .05) were all associated with an increased risk of strabismus. Of the variables analyzed, only cigarette exposure was associated with an increased risk of reduced visual acuity (OR = 4.48; 95% CI: (1.50, 13.4); p < .01) and there was a dose-response relationship. Conclusions : While further study is needed, pediatric providers caring for infants born exposed to buprenorphine and/or maternal smoking during pregnancy should closely follow eye health of children in their early years and be aware that the presentation of strabismus may be subtle.